Cellulose Acetate Butyrate Nanocomposites with Antimicrobial Properties for Food Packaging. (20th June 2012) - Quintero, Rosa Itzela; Rodriguez, Francisco; Bruna, Julio; Guarda, Abel; Galotto, Maria Jose
Abstract : The cellulose acetate butyrate/modified motmorillonite (Cloisite20A and Cloisite30B) nanocomposites were prepared by two different solvent casting methods. All antimicrobial nanofillers were characterized using X‐Ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR) and antimicrobial components (carvacrol and cinnamaldehyde) included in the nanofillers were determined by gas and HPLC chromatography. These analyses confirmed the inclusion of antimicrobial agents in organoclay. The nanocomposite films were characterized by XRD, TGA, Differential Scanning Calorimetry (DSC), Oxygen and Water Vapor Permeability, mechanical properties and antimicrobial behavior against E coli, L.innocua, S. cerevisiae . All films presented a reduction of at least 2.0 log cfu/mL when applied film nanocomposites procedure in which antimicrobial components are included in the last stage of the process and they are not previously included in the organoclay. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : Cellulose acetate butyrate nanocomposites presented a reduction of 1.0, 1.0 and 2.0 log cycles against E. coli, L. innocua and S. cerevisiae respectively (Table 6).